A novel hypothesis for the pathogenesis of glaucomatous disc hemorrhage. (September 2017) - Lee, Eun Jung; Han, Jong Chul; Kee, Changwon
Abstract: Disc hemorrhage is known to be associated with glaucoma development and progression. Several hypotheses have been proposed to explain the pathogenesis of disc hemorrhage in glaucoma, including mechanical and ischemic theories. However, no theory has yet provided a clear explanation of cellular-level events and related histologic findings. Moreover, research has yet to elucidate why glaucomatous disc hemorrhage occurs around the optic disc and at the margin of the retinal nerve fiber layer defect. Understanding the pathogenic mechanism of disc hemorrhage will facilitate interpretation of its clinical importance, and provide better insight into clinical practice. In this review, we sought to provide a plausible hypothesis for the development of glaucomatous disc hemorrhage that could explain the aforementioned characteristic features. We suggest a new and detailed mechanism for disc hemorrhage. Critical microscopic events are also discussed in relation to reactive gliosis in glaucoma. With proliferative reactive gliosis, fibrous glial scar forms, and we suggest that the traction force induced by glial scar formation might disrupt capillary at the border between the healthy and damaged retinal nerve fiber layer, and develop splinter-shaped peripapillary hemorrhage. In addition to glial scar formation, remodeling and deformation of lamina cribrosa beams would insult the capillary surrounding the pore of the lamina cribrosa, and lead to development of round blotch-shaped cup hemorrhage. Histopathologic confirmation of these findings should be explored in future investigations. Highlights: Mechanical disruption of capillaries associated with axonal degeneration may be the source of glaucomatous disc hemorrhage. Reactive gliosis in glaucoma forms gliotic scar, which can contract and generate tractional forces on the capillaries. A subset of disc hemorrhage may be related to deformation of lamina cribrosa pores in glaucoma.